Moral Competence: Challenges in the School Context - Fernandes, Elen Daiane Quartaroli [UNESP]; Martins, Raul Aragão [UNESP] (Springer Nature, 2024)
The objective of this chapter is to contemplate the subject of morality, considering the challenges that schools encounter in cultivating fairness, peace, and the ability for individuals to coexist harmoniously in society, thereby fostering true democracy. Drawing on the theories of Jean Piaget (1932/1948), Lawrence Kohlberg (1992), George Lind (2016), and other theoretical references that emphasize moral development, it is posited that the school environment and education can facilitate the cultivation of this competence. Consequently, the way moral issues are addressed within educational institutions has a direct impact on students’ behavior and the quality of their interpersonal relationships. From these investigations, it is evident that discussing dilemmas in schools can serve as an effective strategy, as it provides individuals with a platform to express their opinions peacefully, even when they differ from those of others. Nevertheless, the lack of sufficient preparation among educators to handle moral issues remains a challenge that must be overcome. Therefore, there is a need for research dedicated to professional training in morality, with the goal of enhancing the quality of teaching practices related to the development of moral competence.